Dysbiotic Co-Factors in Cervical Cancer. How the Microbiome Influences the Development of Cervical Intraepithelial Neoplasia (CIN) - Finzer, Patrick; Küppers, Volkmar; Griesser, Henrik (Geburtshilfe und Frauenheilkunde, 2023)
Human papillomavirus (HPV) infection is a necessary but not sufficient condition for the development of cervical cancer. The dysbiotic shift in the cervicovaginal microbiome appears to be a major co-factor in carcinogenesis. New analytical methods, such as next-generation sequencing (NGS), can be used to detect all of the vaginal microorganisms present and therefore identify individual therapeutic options. The relationship of bacterial vaginosis and carcinogenesis, as well as possible indications for the use of microbiome analysis, will be discussed.Die Infektion mit humanen Papillomaviren (HPV) ist für die Entstehung des Zervixkarzinoms eine notwendige, aber nicht hinreichende Bedingung. Die dysbiotische Verschiebung des zervikovaginalen Mikrobioms stellt offensichtlich einen wesentlichen Co-Faktor in der Karzinogenese dar. Neue Analysemethoden, wie das Next-Generation-Sequencing (NGS), erlauben die Bestimmung der Gesamtheit der vaginalen Mikroorganismen und damit die Ableitung individueller Therapieoptionen. Der Zusammenhang von bakterieller Vaginose und Karzinogenese sowie mögliche Indikationen für den Einsatz der Mikrobiom-Analyse werden diskutiert.
Keywords: vaginales Mikrobiom; HPV-Infektion; CIN-Läsionen